Gerakan Earth Hour Tangerang Dalam Perspektif Politik Lingkungan - Rasyid, Ilham; Felixiani Keviola, Jessica Roma (HK-Publishing, 2020)
In this scientific work, the writer will focus on discussing social movements based on the environment carried out by Non-profit Organizations namely Tangerang Earth Hour can be said as a forum or community that not only stands because of one goal of